Factors Affecting Production Hybrid Maize (Zea mays L.) Production in Morobea Village, Sawerigadi Sub-district, West Muna District - Sri Mingdzura; Sitti Aida Adha Taridala; Hidrawati (International journal of technology and education research, 2025)
This research is based on the fact that the hybrid corn cultivated by the majority of people in Marobea Village, Sawerigadi District, West Muna Regency has the main objective of fulfilling the community's source of economic income. Therefore, hybrid corn production has great opportunities that can be exploited from an economic development perspective. This research aims to find out how much influence the use of inputs has on corn production in Marobea Village. The research location was determined with the consideration that the majority of people in Marobea Village still consistently planted hybrid corn. The total population is 240 heads of families. Based on the Slovin formula, the total sample of corn farmers selected was 38 people. The data analysis used is the Cobb-Douglas production function. The research results show that only the land area variable (X1) has a positive and significant effect on corn production (Y). Meanwhile, the variables number of seeds (X2), amount of fertilizer (X3), amount of pesticide (X4), and number of workers (X5) have no effect on corn production (Y).